Management intensity and temporary conversion to other land‐use types affect plant diversity and species composition of subtropical grasslands in southern Brazil. Issue 4 (4th September 2016) - Koch, Christiane; Conradi, Timo; Gossner, Martin M.; Hermann, Julia‐Maria; Leidinger, Jan; Meyer, Sebastian T.; Overbeck, Gerhard E.; Weisser, Wolfgang W.; Kollmann, Johannes
Abstract: Questions: We investigated the effects of grassland management intensity and temporary conversion to other land uses on abiotic and biotic properties of subtropical grasslands. We used species‐rich permanent grasslands of medium management intensity (PG‐M) as a reference, and asked the following questions: (1) do permanent grasslands with low and high management intensities (PG‐L and PG‐H, respectively) have different plant diversity and species composition than reference grasslands; and (2) do secondary grasslands recovering from conversion to arable fields (SG‐A) or pine plantations (SG‐P) differ from permanent grasslands in their plant species composition and abiotic conditions? Location: Highland grasslands, Campos de Cima da Serra, Rio Grande do Sul (RS), Brazil. Methods: We analysed variation in plant species composition and diversity among 80 grassland sites, including three types of permanent grassland and two types of secondary grassland. An indicator species analysis was used to identify characteristic species for the different land‐use types. We used a linear discriminant analysis to investigate differences in soil conditions among land‐use types. Results: Both PG‐L and PG‐H differed from PG‐M regarding plant species composition. Although PG‐L shared many typical grassland species with PG‐M, their communities were generally less diverse. PG‐H, on the other hand, not only had fewer species but also deviated from PG‐M in species composition. Secondary grasslands on former arable fields and plantations differed from PG‐M in species composition and showed lower diversity. Soil conditions of SG‐P were similar to those of PG‐L and PG‐M, but they were distinct from those of PG‐H and SG‐A. Conclusions: All land‐use types showed deviations from reference grasslands (PG‐M). The decrease in the number of species in PG‐L may be reversed if traditional management intensity is re‐introduced, whereas strong compositional changes in SG‐P may require the re‐introduction of grassland species. This is also true for PG‐H and SG‐A: both showed marked deviations from reference grasslands in biotic and abiotic components. Overall, restoration of altered land‐use types to near‐natural subtropical grassland seems feasible, but suitable techniques have to be developed. Abstract : We assessed the potential of former arable fields and pine plantations for the restoration of subtropical grasslands and found that both were lacking essential similarity to native communities. Looking at different types of management we also evaluated which types can maintain a diverse grassland community and which types lead to degradation of the grassland.